Walking the streets of a virtual metropolis. The audiosphere of the game Grand Theft Auto IV - Kopaniecki, Jakub (Interdisciplinary Studies in Musicology, 2019)
On the basis of works devoted to the topic of sound studies and video games, the author presents ways of processing and using sounds in order to create virtual phonic spaces. He examines the means by which contemporary game developers influence immersivity, i.e., the process of immersing the gamer in virtual environments, as well as indicating the mutual influences of audial and visual spheres. Analysig the video game Grand Theft Auto IV from the perspective of the sound which accompanies the action, he compares in this respect three areas of the game’s Liberty City with their equivalents in New York on which the virtual city is modelled. The similarities and differences between the digital and virtual spaces are identified, and the reasons for them explained. This makes it possible to show how the use of the tools (explained earlier) employed by the developers of the game enable them to create a credible sounding virtual metropolis.